Beggars Bush: A Comedy : From the Works of Francis Beaumont and John Fletcher (Volume 2 of 10) - Fletcher, John, 1579-1625; Beaumont, Francis, 1584-1616 (Salt Lake City, UT : Project Gutenberg, 2004)
"Beggars Bush: A Comedy by John Fletcher and Francis Beaumont" is a Jacobean stage play first performed in 1622. In a fictional Flanders, a usurper has seized the throne, forcing the rightful royal family into hiding. The rightful heir's father disguises himself as king of the beggars, while other characters maintain secret identities. Through disguises, hidden nobles, and a romanticized underworld of beggars and thieves, the play weaves political intrigue with comedy as characters work toward restoring the legitimate rulers and reuniting separated lovers. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Beggars%27_Bush
Release date is 2004-04-01
Produced by Jonathan Ingram, Jonathan Ingram, Charles M. Bidwell and the Online Distributed Proofreading Team
Keywords: Comedy plays; English drama -- 17th century